EVALUASI KINERJA LULUSAN KEPERAWATAN KUPANG POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN KUPANG OLEH STAKEHOLDER DI KOTA KUPANG TAHUN 2014 - IRFAN IRFN; YUANITA CLARA LUHI ROGALELI (JURNAL INFO KESEHATAN, 2015)
Nursing Department at Kupang Health Polytechnic of Health Ministry has a very an important role in producing professional prospective nurses in the field. The graduates of Nursing Department at Kupang Health Polytechnic of Health Ministry are expected not only to have competencies of nursing but also have the professional ethics and mastered information technology so that they can compete with graduates from other medical colleges. For this reason, the Nursing Department at Kupang Health Polytechnic of Health Ministry conducted an evaluation of its graduate’s performance in order to get input for the implementation of education and learning process so that the qualified graduates can be produced in line with the job market demands. This research is a descriptive study and the sample is the direct supervisors of the graduates from Nursing Department at Kupang Health Polytechnic who graduated in 2002-2013 and are working in health facilities both public and private in Kupang City. The research variables include the Graduates’ performance with the type of Graduates’ ability adopted from Colleges Accreditation Forms, which are integrity (ethics and moral), science-based expertise (core competencies), English, use of information and technology, communication, teamwork, and self-development. This research is a descriptive study and the sample is the direct supervisors of the graduates from Nursing Department at Kupang Health Polytechnic who graduated in 2002-2013 and are working in health facilities both public and private in Kupang City. The research variables include the Graduates’ performance with the type of Graduates’ ability adopted from Colleges Accreditation Forms, which are integrity (ethics and moral), science-based expertise (core competencies), English, use of information and technology, communication, teamwork, and self-development. Based on the study results, it can be concluded that: the user feedback on the performance of graduates from Nursing Department at Kupang Health Polytechnic who worked in Kupang City for the type of Integrity (ethics and moral), science-based expertise/ professionalism and core competencies, communication, use of information and technology, teamwork, and self-development are mainly good, while the English proficiency are mainly adequate. The type of graduates’ performance capabilities that needs to be improved in order to improve the quality of graduates from Nursing Department Nursing Department at Kupang Health Polytechnic who work in Kupang city is to improve the ability to speak English.